The Game “Quiz Besemah” Sebagai Media Untuk Memperkenalkan Budaya Kota Pagar Alam - Lendy Rahmadi; Medi Triawan (Universitas Bina Darma, 2021)
Pagar Alam City has great potential in the field of tourism, both natural and cultural tourism. Pagar Alam City is also known as one of the Besemah tribal areas with various cultural heritages. Game